Optimization of culture conditions for tannase production by Aspergillus sp. gm4 in solid state fermentation - Patrícia Nirlane da Costa Souza; Natália da Costa Maia; Luís Henrique Souza Guimarães; Mário Lúcio Vilela de Resende; Patrícia Gomes Cardoso (Acta Scientiarum. Biological Sciences, 2015)
Tannase is an industrially important enzyme produced by a large number of microorganisms. This study analyzed the production of tannase by Aspergillus sp. GM4 under solid-state fermentation (SSF) using different vegetable leaves (mango, jamun and coffee) and agricultural residues (coffee husks, rice husks and wheat bran). Among the substrates used jamun leaves yielded high tannase production. The Plackett-Burman design was conducted to evaluate the effects of 12 independent variables on the production of tannase under SSF using jamun leaves as substrate. Among these variables, incubation time, potassium nitrate and tannic acid had significant effects on enzyme production. A lower incubation time was fixed and supplementation with potassium nitrate and tannic acid were optimized using the Central Composite Design. The best conditions for tannase production were: incubation time of 2 days; tannic acid at 1.53% (w w-1) and potassium nitrate at 2.71% (w w-1). After the optimization process, tannase production increased 4.65-fold, which showed that the statistical experimental design offers a practicable approach to the implementation of optimization of tannase production.